Longitudinal genomic analysis of Neisseria gonorrhoeae transmission dynamics in Australia - Mona L. Taouk; George Taiaroa; Sebastian Duchene; Soo Jen Low; Charlie K. Higgs; Darren Y. J. Lee; Shivani Pasricha; Nasra Higgins; Danielle J. Ingle; Benjamin P. Howden; Marcus Y. Chen; Christopher K. Fairley; et al. (Nature Communications, 2024)
Abstract N. gonorrhoeae, which causes the sexually transmissible infection gonorrhoea, remains a significant public health threat globally, with challenges posed by increasing transmission and antimicrobial resistance (AMR). The COVID-19 pandemic introduced exceptional circumstances into communicable disease control, impacting the transmission of gonorrhoea and other infectious diseases. Through phylogenomic and phylodynamic analysis of 5881 N. gonorrhoeae genomes from Australia, we investigated N. gonorrhoeae transmission over five years, including a time period during the COVID-19 pandemic. Using a novel cgMLST-based genetic threshold, we demonstrate persistence of large N. gonorrhoeae genomic clusters over several years, with some persistent clusters associated with heterosexual transmission. We observed a decline in both N. gonorrhoeae transmission and genomic diversity during the COVID-19 pandemic, suggestive of an evolutionary bottleneck. The longitudinal, occult transmission of N. gonorrhoeae over many years further highlights the urgent need for improved diagnostic, treatment, and prevention strategies for gonorrhoea.